EU trade agreements: to mix or not to mix, that is the question - Conconi, P; Herghelegiu, C; Puccio, L (Kluwer Law International, 2021)
The European Union (EU) can only act internationally on competences that have been transferred to it by its Member States. Trade agreements negotiated by the EU that include provisions outside its exclusive competences should be concluded as ‘mixed’. Mixed trade agreements must be ratified following not only the procedures set out in the EU treaties, but also the national ratification procedures of the Member States. As a result, national or even regional parliaments may block trade deals agreed between the EU and its trading partners after years of negotiations. Should the EU then avoid negotiating mixed trade agreements? We argue that the answer to this question depends crucially on the objectives of the EU when negotiating with its trading partners. If the EU is mostly driven by market-access motives, it should restrict the agreement to policy areas under its exclusive competence, thus insulating the trade deal from the legal and political risks of mixity. When instead its motives are mostly political, mixity is a ‘necessary evil’ to achieve non-trade objectives.